2016
DOI: 10.5267/j.ijiec.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of surface roughness and cutting force during turning of Ti6Al4V ELI in dry environment

Abstract: This paper investigates the effect of cutting parameters on the surface roughness and cutting force of titanium alloy Ti-6Al-4V ELI when turning using PVD TiAlN coated tool in dry environment. Taguchi L9 orthogonal array design of experiment was used for the turning experiment 2 factors and 3 levels. Turning parameters studied were cutting speed (50, 65, 80 m/min), feed rate (0.08, 0.15, 0.2 mm/rev) and depth of cut 0.5 mm constant. Linear and second order model of the surface roughness and cutting force has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Besides, the CFRP-Ti alloy stack is one of the popular hybrid materials used commonly in aerospace applications which requires unique tools and a special machining strategy [3][4][5][6][7]. In the dry turning experiment performed by Sargade et al [8] on Ti6Al4V at low-medium speed, they have found that feed rate has the highest significance on surface roughness and forces followed by cutting speed. A higher cutting speed and lower feed rate gave a superior surface finish.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the CFRP-Ti alloy stack is one of the popular hybrid materials used commonly in aerospace applications which requires unique tools and a special machining strategy [3][4][5][6][7]. In the dry turning experiment performed by Sargade et al [8] on Ti6Al4V at low-medium speed, they have found that feed rate has the highest significance on surface roughness and forces followed by cutting speed. A higher cutting speed and lower feed rate gave a superior surface finish.…”
Section: Introductionmentioning
confidence: 99%
“…Revankar et al (2014) observed that the surface roughness is minimum in MQL environment as compared to dry and wet condition. Sargade et al (2016) observed that the feed was the most dominant factor for surface roughness having 97.34% contribution during turning the Ti6Al4V ELI by using PVD TiAlN insert in dry environment. Shetty et al (2014) reported that the impact of lubrication was highest physically as well as statistical influence on surface roughness of about 95.1% when turning Ti6Al4V by implementing PCBN tool under dry and near dry condition.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium-based alloys possess high corrosion resistance, hot hardness, and wear resistance [2]. Even though many favourable properties of titanium *Corresponding Author Institutional Email: suresh.nipanikar@kbpcoes.edu.in (S. Nipanikar) alloys are still very difficult to machine due to their inherent properties such as high strength and hardness at elevated temperature, low thermal conductivity, low modulus of elasticity, self-induced chatter, work hardening behaviour, and chemical reactivity with various materials at elevated temperatures [3]. Various literature has commented on the poor machining behaviour of titanium alloys.…”
Section: Introductionmentioning
confidence: 99%